Impacts of climate warming, pollution, and management on the vegetation composition of Central European beech forests - Daniel Scherrer; Roland Lüthi; Harald Bugmann; Jacques Burnand; Thomas Wohlgemuth; Andreas Rudow (Ecological Indicators, 2024)
Over the past century, climate warming, nitrogen deposition, acidic rain, widespread disturbance events, adaptive management, and natural stand maturation have substantially altered the composition and structure of forests. However, the absence of historical data on the environment makes it difficult to prove these long-term effects. Ecological indicator values based on plant species characteristics offer a promising approach to detect presumed changes at relevant spatial scales (i.e., site level). In this study, we discerned the shifts in taxa composition of principal Central European beech forests and their associated environmental drivers by integrating three data sources: (1) 254 historical (1937 – 1948) and resurveyed (2019 – 2022) vegetation relevés of beech-dominated forests sites in the Swiss Jura mountains, (2) derived ecological indicator values for vascular plants regarding temperature, soil moisture, micro-climatic conditions, soil nutrients, pH, humus layer, and light availability, and (3) related data on disturbance/management intensity in these forest sites over the past 75 years, categorized as ‘undisturbed’ and ‘disturbed’ sites. We found a significant decrease in alpha diversity (taxa richness per site) on ‘undisturbed’ sites (loss of 7.0 ± 1.48 taxa) but stability on ‘disturbed’ sites (gain of 2.1 ± 5.71 taxa). Both beta (Jaccard dissimilarity) and gamma diversity (overall taxa richness) increased over the study period. The average ecological indicator values per site (EIV‾s) consistently indicated climate warming impacts on all sites ranging from 390 to 1480 m a.s.l., while effects of acidic rain on soil pH and nitrogen deposition on soil fertility were negligible, except in densely populated lowland forest areas. The EIV‾s for light and micro-climatic conditions differed between ‘undisturbed’ and ‘disturbed’ sites, indicating darker and more oceanic, and more open and continental conditions, respectively. The decrease in alpha diversity on ‘undisturbed’ sites corresponded primarily with reduced light availability, suggesting that stand maturation is the main driver of taxa loss while climate warming and pollution mainly affected composition rather than taxa richness. In contrast, the rise in beta and gamma diversity likely stems from changes in forest management and disturbance regimes, which have increased structural diversity with various micro-climatic niches enriching the taxa pool. In conclusion, our study demonstrates the ability to differentiate the profound effects of climate warming and pollution agents on forest composition and underscores the critical role of adaptive management in mitigating these impacts. By fostering structural diversity and biodiversity, adaptive management enhances the resilience of forests, enabling them to better adapt to evolving environmental conditions.